Multiobjective analysis of green-blue water uses in a highly utilized basin: case study of Pangani Basin, Africa - Kiptala, J.K.; Mul, Marloes L.; Mohamed, Y.A.; Zaag, P. van der (American Society of Civil Engineers, 2018)
The concept of integrated water resource management (IWRM) attempts to integrate all elements of water resources. Different tools are developed to assist in developing sound IWRM plans. One such tool is multiobjective analysis using an integrated hydro-economic model (IHEM). However, IHEM mainly deals with the optimization of river flow (blue water) in a river basin. This paper linked a distributed model of green water (landscape water uses) in the upper catchment with mainly blue water uses in the lower catchment of the Pangani Basin. The results show that agricultural water use has the highest water productivity and competes with all other objective functions in the catchment. The generation of firm energy competes with the downstream ecosystem requirements. The integrated study shows that improving rainfed cropping through supplementary irrigation has comparable marginal water values to full-scale irrigation but are much higher compared with hydropower. However, hydropower has more benefits if used in conjunction with the environment. The methodological approach has increased the understanding of trade-offs between green and blue water uses that are highly interdependent in African landscapes.